The spatial and seasonal variation of trace metals in coastal seawater and soft tissue of Chthamalus montagui around the northwest coast of Portugal - Reis P.A. (2017)
Metal concentrations (Cd, Cr, Cu, Fe, Mn and Zn) were determined in seawaters and soft tissues of Chthamalus montagui from the northwest coast of Portugal during the four seasons of 2011. The main objectives of this work were to assess seasonal and spatial variations of metals in order to detect hot spots of contamination, to establish correlations between metals in coastal seawaters and C. montagui and to calculate metal bioaccumulation factors (BAFs) in each season. Metal concentrations in coastal seawaters ranged within Cd: 1.2–35 ng L−1; Cr: 15–87 ng L−1; Mn: 77–1763 ng L−1; Cu: 126–1819 ng L−1; Fe: 430–4048 ng L−1 and Zn: 2889–16867 ng L−1 and in C. montagui ranged for Cd: 0.39–1.98 mg kg−1; Cr: 0.45–3.13 mg kg−1; Cu: 0.93–5.70 mg kg−1; Mn: 2.2–20.4 mg kg−1; Fe: 135–707 mg kg−1 and Zn: 119–782 mg kg−1. Significant spatial and seasonal variations were found between: (i) metal concentrations in seawaters and C. montagui tissues; (ii) the distribution of metal concentrations in C. montagui tissues were Fe > Zn > Mn > Cu > Cr > Cd and (iii) C. montagui showed higher bioaccumulation factors for Fe and Cd than for Cu, Mn and Zn in all seasons. Regarding the metal concentrations accumulated in C. montagui tissues during each season of 2011, the ecological quality classifications of the NW coast of Portugal varied from “Class I–Unpolluted” to “Class III–Remarkably Polluted”. © 2017, Korea Institute of Ocean Science & Technology (KIOST) and the Korean Society of Oceanography (KSO) and Springer Science+Business Media